Examining university students' attitudes towards fat phobia - Emre Turegun; Huseyin Ozturk; Recep Sarıkaya; Yakup Afyon (Türk Spor ve Egzersiz Dergisi)
The aim of this study was to determine the levels of college students and to examine fat phobia. The sample ofthis study was 219 men and women university students from School of Physical Education and Sport inÇanakkale Onsekiz Mart University. Participate were first, second, third and fourth grade. A short form of thefat phobia scale as the data collection tool was used. One Way Anova and unpaired t-test were used comparevariables. According to the results of this study, students' fat phobia level (3.06 ± 0.44) was found at moderatelevels. A significant difference between male and female students' attitudes fat phobia was not found (p gt; 0.05).In conclusion, obese and overweight people are the most important cause of the social adversities, exhibit anegative attitude towards other people are obese and more people are thought to arise.